Maximizing the expression of transgenic traits into elite alfalfa germplasm using a supertransgene configuration in heterozygous conditions - Jozefkowicz, Cintia (2018)
Numerous species of legumes, including alfalfa, are critical factors for agroecosystems due to their ability to grow without nitrogen fertilizers derived from non-renewable fossil fuels, their contribution of organic nitrogen to the soil, and their increased nutritional value. Alfalfa is the main source of vegetable proteins in meat and milk production systems worldwide. Despite the economic and ecological importance of this autotetraploid and allogamous forage crop, little progress has been made in the incorporation of transgenic traits into commercial alfalfa. This is mainly due to the unusually strong transgene silencing and complex reproductive behavior of alfalfa, which limit the production of events with high transgene expression and the introgression of selected events within heterogeneous synthetic populations, respectively. In this report, we describe a novel procedure, called supertransgene process, where a glufosinate-tolerant alfalfa variety was developed using a single event containing the BAR transgene associated with an inversion. This approach can be used to maximize the expression of transgenic traits into elite alfalfa germplasm and to reduce the cost of production of transgenic alfalfa cultivars, contributing to the public improvement of this legume forage and other polyploid and outcrossing crop species.